Depiction of Digital Safety Issues Between Parents and Adolescent in Banten Province - Yenie Wulandari (Jurnal Riset Public Relations, 2022)
Abstract. The rise of information technology provokes problems around the use of incorrect information flows that could lead to a dangerous circumstance. Data from a study conducted by KPAI in 2011-2014 reported 932 characteristics of pornography and cyber-crime that made children the main target. Hence, parents and adolescent must understand how to protect their teens in the abuse of social media. However, according to digital literacy survey that was held by Kominfo, the central part of Indonesia, such as Bali, Kalimantan and Sulawesi, has a relatively better digital literacy status compared to the western and eastern regions. Furthermore, the survey also stated that Banten is an area with a lower score when compared to Eastern regions such as Maluku and Papua regarding information and data literacy (Kominfo, 2020). Therefore, this mini research was conducted in Banten Province in order to understand the level of vulnerability of social media usage among adolescents and the level of parental understanding of online safety in the use of social media. This study used quantitative approaches in order to understand the challenges faced by parents and adolescent regarding media literacy. The result showed that parental control strategies are urgently needed so that adolescents are not negatively affected by social media. Furthermore, there is a need to organize activities or workshops to improve digital literacy skills for both parents and adolescent in Banten Province.